PEMANFAATAN KOTORAN TERNAK MENJADI SUMBER ENERGI ALTERNATIF DAN PUPUK ORGANIK - R. Amaranti; M. Satori; Y.S. Rejeki (BUANA SAINS, 2012)
Enviromental problems due to activities of exploration and exploitation of natural resources for energy and utilization of energy as source of fuel become importance issue in Indonesia. Therefore an alternative for utilization of natural resources as energy is desperately needed. One of the potential resources is utilization of manure as energy alternative and fertilizer. Society of Sindangbarang village, Sub district Jalaksana of Kuningan District generally is farmer and husbandary with main activities on goat cattle. Social guidance was conducted to utilize manure as sources for energy and liquid fertilizer. The social guidance activieties were divided into three steps, i.e. identification, implementation and evaluation. Implemention was main step to install digester for processing goat manure to make biogas. The results indicated that goat manure as biogas could be made as fuel energy for cooking and organic fertilizer as alternative for agriculture activities. It is concluded that a large positive affect will be gained if all goat farmers do the same way and this avtivities is also to support government policy for alternative energy, organic agriculture and improving environmental life condition